Effectiveness of a family-centered empowerment-based digital pocketbook on self-efficacy and iron supplement adherence among pregnant women: A quasi-experimental study - Ariska Fauzianty; Friza Novita Sari Situmorang; Sonia Novita Sari; Siti Sabiah; Vivi Restiyani Hasibuan; Yuliska Febriyan (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Pregnancy-related anemia remains a major public health problem in Indonesia, largely attributable to low iron supplementation adherence among pregnant women. Evidence regarding digital interventions based on the family centered empowerment model (FCEM) remains limited. This study aimed to evaluate the effectiveness of an FCEM-based digital E-Pocket Book in improving self-efficacy and adherence to iron tablet consumption among pregnant women. A quasi-experimental pretest–posttest control group study was conducted at the Sentosa Baru Community Health Center in Medan, Indonesia, from July to August 2025. A total of 50 pregnant women (gestational age, 14–36 weeks) were allocated to an intervention group (n = 25) and a control group (n = 25). The intervention group received the FCEM-based E-Pocket Book for four weeks, while the control group received standard antenatal education. Data were analyzed using the Wilcoxon signed-rank and Mann–Whitney U tests. The intervention group demonstrated significantly greater improvements in self-efficacy (p = 0.027; d = 0.78) and adherence to iron supplementation (p = 0.001; d = 0.91) than the control group. In conclusion, the family-centered empowerment–based digital pocketbook is effective in improving self-efficacy and adherence to iron supplementation among pregnant women.